Evaluation Of Anti-Inflammatory And Anti-Arthritic Activities Of Semecarpus Anacardium In Experimental Animals (Journal of Pharmaceutical Negative Results, 2023)
Background: Arthritis is a joint inflammation, either temporary or persistent and may manifest in a variety of ways, each requiring a tailored approach to treatment. The objective of this research was to examine the anti-inflammatory, anti-allodynic, and anti-arthritic properties of Semecarpus anacardium nuts in carrageenan-induced paw edema and adjuvant-induced arthritis.Methodology: The anti-inflammatory effects of S. anacardium nut extracts were determined in a rat model of inflammation using carrageenan-induced paw edema. The anti-allodynic activity was studied using von Frey test. The animal's withdrawal of its paw was seen as a positive response when von Frey filament was placed on the plantar portion of the rat's hind paw from its base. Arthritis was induced in rats through inoculation with Freund's complete adjuvant (CFA). Erythrocyte sedimentation rate (ESR), platelet count, and red blood cell count are the haematological markers evaluated to study adjuvant-induced arthritis. For evaluating the antioxidant activity, total antioxidant content (TAC) and ferrous reducing antioxidant content (FRAC) were estimated.Results: Treatment with natural extract of S. anacardium (NESA) low and high doses and the standard drug have shown a decrease in paw volume compared to the diseased group. In von frey test, from 30 min onwards all the treatment groups have shown significant increase in paw withdrawal threshold (p < 0.001) when compared to carrageenan control group. Induction of arthritis caused an increase in WBC, ESR and platelet count, and decrease in RBS count in AIA control group. S. anacardium improved all of these parameters. At the concentration of 150 μg/mL, the absorbance in TAC assay was in range of 1.164 ± 0.065 - 1.694 ± 0.039, while in FRAC assay, the absorbance was in range of 1.774 ± 0.046 - 2.992 ± 0.127.Conclusion: This research established that S. anacardium's physiologically active components, including steroids, flavonoids, polysaccharides, phenols, and terpenes, are responsible for its anti-inflammatory effects and may be able to lessen FCA-induced arthritis.